Hukuman Kebiri Kimia bagi Pelaku Kekerasan Seksual terhadap Anak dalam Perspektif Hukum Islam - Ahmad Habib Al Fikry (Jurnal Hukum Lex Generalis, 2021)
Chemicals a punishment for perpetrators of sexual violence against children or pedophiles. Pedophilia is abnormal sexual behavior by making children the object of satisfying sexual desire. Data on sexual violence against children in Indonesia shows an alarming number. Such actions certainly injure human rights, especially child protection, and are contrary to statutory regulations. The state provides legal certainty and upholds justice through the existence and enactment of laws and regulations concerning child protection. One of the discourses regulated in it is about criminal sanctions for perpetrators of sexual violence against children in order to provide a deterrent effect and stop the act. Chemical castration is one of the criminal sanctions that threaten pedophiles. The procedure for this action is regulated more specifically in the Government Regulation of the Republic of Indonesia Number 70 of 2020. The adoption of this regulation as an implementer of the previous regulation reaps pros and cons from the community. The author's interest in researching this discourse from the perspective of Islamic law gives the answer that chemical castration punishment is a tadzir punishment. In determining punishment for an act, Islamic criminal law recognizes the existence of formal, material and moral considerations. Sexual violence against children is an act that is considered to have fulfilled these three elements so that it can be subject to punishment or Jarimah. Pedophile punishment is Jarimah tadzir, which is a sentence decided by a judge in order to provide education and preventive measures for the perpetrator from committing another crime.